Commentary: Gene by environment interplay and psychopathology – in search of a paradigm. (5th September 2013) - Nigg, Joel T.
Abstract : The articles in this Special Issue (SI) extend research on G×E in multiple ways, showing the growing importance of specifying kinds of G×E models (e.g., bioecological, susceptibility, stress‐diathesis), incorporation of sophisticated ways of measuring types of G×E correlations ( r GE), checking effects of statistical artifact, exemplifying an impressive range of quantitative and biological methodologies, and pointing to clearly needed next‐step studies such as summarizing across many genes in gene sets ( Bentley et al.2 ) or in genome‐wide pathway based approaches to G×E ( Winham & Biernacka ) and prediction of clinical outcomes ( Rapee et al. ) . As a group, they document nicely that gene × environment research has come of age. What is the import of this? Does it represent a major new development in our field, or merely an incremental change of a framework that remains fundamentally unchanged?